Perceptions and behaviors of healthcare providers towards rehabilitation support to children with severe malaria-related disability in Ethiopia: A qualitative descriptive study using the Theoretical Domains Framework - Engeda, Eshetu Haileselassie; Aldersey, Heather M; Davison, Colleen M; Gelaye, Kassahun Alemu; Fayed, Nora (Public Library of Science, 2024)
Abstract INTRODUCTIONSevere malaria often results in childhood disability. The prevalence of disability related to severe malaria is significant and is estimated to affect up to 53% of severe malaria survivors. In contrast, information is sparse about how healthcare providers in Africa think about or provide rehabilitation support in acute and post-acute phases respectively. Understanding the perceptions and behaviors of healthcare providers treating malaria could help inform malaria-related disability research, policy, and practice, aimed at the providers themselves. This study explored the perceptions and behaviors of healthcare providers towards rehabilitation for children with severe malaria-related disability. The Theoretical Domains Framework was used to describe the findings relative to wider literature on health provider behavior change.METHODSA qualitative descriptive approach was used to interview thirteen healthcare providers recruited purposively based on their clinical professions, roles, and settings. Data were analyzed using directed content analysis. We decided on the most prominent theoretical domains considering the frequency of specific perceptions and behaviors across the participants, the frequency of perceptions and behaviors in each domain, and evidence of strong perceptions and behaviors.RESULTSNine out of fourteen theoretical domains were identified. These domains were: Beliefs about consequences, environmental context and resources, goals, knowledge, skills, optimism, reinforcement, social influences, and social or professional role and identity. Healthcare providers' beliefs about their roles in screening for disability or referring to rehabilitation were less positive.CONCLUSIONSThe findings of this study suggest the need for interventions to support healthcare providers in acute phases (prevention and control of severe malaria) and post-acute phases (disability screening, referral, and rehabilitation care). Recommended interventions should focus on developing clinical guidelines, training clinicians, addressing institutional factors, and modifying external social influences such as socio-cultural factors. MEDLINE - Academic
Keywords: Severe malaria; childhood disability; healthcare providers in Africa; socio-cultural factors.